TECHNOLOGICAL PLATFORM FOR MODERNIZING FOOD INDUSTRY UN RUSSIAN AGROINDUSTRIAL COMPLEX UNDER REAL BIOCENOSE, MARKET, AND WTO - Andrei Georgievich Khramtsov; Ivan Alekseevich Yevdokimov; Svetlana Andreevna Ryabtseva; Valentin Ivanovich Shipulin; Aleksei Dmitrievich Lodygin (Вестник Северо-Кавказского федерального университета, 2022)
The article offers a view on the contribution that the scientific school Life Sciences has made in the modernization of the food industry in the Russian Federation. It also presents innovative developments in the field of processing raw food stuff of animal origin. There is a formulation of a paradigm for developing a technology platform for processing agricultural raw material of animal origin.